Regional changes of climate and atmospheric circulation and balanse of mass of small glacier at Galindez Island - V. E. Tymofeyev; V. F. Grishchenko (Ukrainian Antarctic Journal, 2010)
The effect of the ElNiño on the glacial climate of the region is discussed. Negative air temperature anomalies at Antarctic Peninsula with predominant accumulation are formed in positive ENSO phase, and positive air temperature anomalies with predominant ablation are formed under LaNiña conditions. Difference in the meteorological regime between the western coast of Antarctic Peninsula is noted and the need for continuing research into coastal and internal regions of the Antarctic Peninsula is stressed.